Clinical effective risks of mortality in road traffic injury victims depending on the severity of damage - S.O. Guryev; V.A. Kushnir; O.S. Solovyov (Хірургія дитячого віку)
Road traffic accidents cause significant trauma to the population and are one of the main causes of mortality in working age. The novelty of the study risk-oriented patterns of severity of damage and mortality of victims of road accidents have been established.